2008
DOI: 10.1002/art.24162
|View full text |Cite
|
Sign up to set email alerts
|

Recovery: What does this mean to patients with low back pain?

Abstract: Objective. To explore patients' perceptions of recovery from low back pain, about which little is known. Methods. A qualitative study was conducted in which 36 participants, either recovered or unrecovered from low back pain, participated in focus groups. Interviews were audiorecorded and transcribed verbatim. Framework analysis was used to identify emergent themes and domains of recovery. Results. Patients' views of recovery encompassed a range of factors that can be broadly classified into the domains of sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 32 publications
8
113
1
Order By: Relevance
“…Both of these scenarios could result in different conclusions regarding GPE than what might be observed in other settings. The fact that our observations are similar to previous research in low back pain [8] diminishes this concern.…”
Section: Strengths and Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…Both of these scenarios could result in different conclusions regarding GPE than what might be observed in other settings. The fact that our observations are similar to previous research in low back pain [8] diminishes this concern.…”
Section: Strengths and Limitationssupporting
confidence: 91%
“…This is supported by qualitative research demonstrating that low back pain patients cognitively appraise their symptoms, daily activities and quality of life when considering their recovery [8]. This is likely similar for those suffering from neck pain, where multiple factors have been shown to impact patients' experiences and behaviors [9].…”
Section: Introductionmentioning
confidence: 95%
“…13 Schiller et al interviewed patients following hip fracture who described seeking support, moving more and preserving perspective as the fundamental factors in improving outcome, 26 whereas other studies reported that psychological health was considered by patients as an important marker of recovery. 27,28 Although we did not specifically target questions to determine quality of life factors or personality traits, interestingly, in this population, those discharged home commonly reported that family support and their own strength of mind and determination were the major factors in achieving their goals, whereas those discharged to in-patient rehabilitation seemed to focus on the importance of others in their recovery, often claiming that it was the rehabilitation staff who were the reason for their positive outcome. Locus of control appears to be an individual trait that does not change with different situations, especially with regard to health-related matters.…”
Section: Discussionmentioning
confidence: 99%
“…While participants did not question the validity of the iBAQ questionnaire, there is increasing concern that the similar patient-reported outcome measures used in back pain trials may not measure aspects that are important to patients. [16][17][18] For clinical trial interpretation to be maximised, this needs to be a focus of future research.…”
Section: Strengths and Limitationsmentioning
confidence: 99%